Aktivitas Antioksidan Ekstrak Astaxanthin dari Limbah Kulit dan Kepala Udang Dogol (Metapenaeus ensis) - Rahmalia, Winda; Adhitiyawarman, Adhitiyawarman; Prayitno, Dwi Imam; Lubis, Yosef Novem Batistuta (Jurnal Kelautan Tropis, 2024)
Astaxanthin is a carotenoid derivative compound with various benefits, one of which is as an antioxidant, making astaxanthin applicable in drugs and cosmetics. Astaxanthin is discoverable in various sources, with shrimp as its main source. This study aims to determine the antioxidant activity of astaxanthin extracted from shrimp shell and head wastes. Extraction was carried out using the soxhletation method, followed by saponification to obtain free astaxanthin. Astaxanthin in extract before and after saponification were identified using thin-layer chromatography (TLC) and UV-Vis spectrophotometry. Antioxidant activity assay was carried out in five variations of sample concentrations using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Extraction of shrimp shell and head wastes resulted in an oil yield percentage of 1.02 and 3.05 % of dry mass in 60 g of shrimp shells, respectively. Identification results showed astaxanthin content in extracts after saponification were higher than that before saponification. There are three thin layer chromatography (TLC) separation spots and two UV-Vis absorption peaks in extracts before and after saponification. Antioxidant activity assay results (IC50) of shrimp shell extract before and after saponification showed antioxidant activity of 572.0 and 186.6 mg/L, respectively. Astaxanthin merupakan senyawa turunan karotenoid dengan beragam manfaat, salah satunya sebagai antioksidan, sehingga membuat astaxanthin dapat diaplikasikan dalam obat-obatan dan kosmetik. Astaxanthin dapat ditemukan dalam berbagai sumber, dengan sumber utama adalah udang. Penelitian ini bertujuan untuk menentukan aktivitas antioksidan astaxanthin yang diekstraksi dari limbah kulit dan kepala udang. Ekstraksi dilakukan dengan metode soxhletasi, dilanjutkan dengan saponifikasi untuk mendapatkan astaxanthin bebas. Hasil ekstraksi dan saponifikasi diidentifikasi astaxanthinnya menggunakan kromatografi lapis tipis (KLT) dan spektrofotometri UV-Vis. Uji aktivitas antioksidan dilakukan pada lima variasi konsentrasi sampel menggunakan metode 2,2-difenil-1-pikrilhidrazil (DPPH). Ekstraksi limbah kulit dan kepala udang menghasilkan rendemen masing-masing sebesar 3,05 dan 1,02% massa kering dari 60 g kulit udang. Hasil identifikasi menunjukkan kadar astaxanthin dari ekstrak setelah saponifikasi lebih tinggi daripada sebelum saponifikasi. Terdapat tiga spot pemisahan kromatografi lapis tipis (KLT) serta dua puncak serapan UV-Vis pada ekstrak sebelum dan setelah saponifikasi. Hasil uji aktivitas antioksidan (IC50) kulit udang sebelum dan setelah saponifikasi masing-masing adalah 572,000 dan 186,583 mg/L.